S21 Type-2 Innate lymphoid cells induce CD4 T helper cell type-2 immune functions. (14th November 2013) - Mirchandani, AS; Besnard, AG; Yip, E; Scott, C; Bain, C; Salmond, RJ; Liew, FY
Abstract : Introduction: Type-2 innate lymphoid cells (ILC2) are a novel subset of immune cells characterised by their responsiveness to interleukin (IL)-33 and their production of type-2 cytokines (including IL-5, IL-9, IL-13). ILC2 have a variety of roles in lung inflammation and repair. Their interaction with innate immune cells has been shown, however their influence on the adaptive immune system remains unknown. Given the important roles of CD4 T helper (Th) cells in the lung and in conditions such as asthma, it is vital to determine whether ILC2 can influence their functions. Aim: To determine the interactions of lung-derived ILC2 cells on naïve Th functions. Method: BALB/c mice were treated with IL-33 intranasally for 5 days and ILC2 cells were sorted using fluorescence-activated cell sorting (FACS). Naïve Th cells were sorted by FACS from ST2 knockout mice (lacking the IL-33 receptor). Cells were co-cultured in the presence of anti-CD3 and anti-CD28 antibody for 72 hours. Intracellular cytokines were determined by FACS following phorbol 12-myristate 13-acetate (PMA) and ionomycin stimulation. Th cells were differentiated from ILC2 by their expression of CD4 and lack of ST2. Results: Naïve Th cells expression of type-2 cytokines increases significantly when cultured with ILC2 cells (Fig.1 ). Th cell IL-4 expression increases 3-fold in co-culture, whilst IL-5 and IL-13 expression are enhanced 30- and nearly 20-fold, respectively. This effect is completely abrogated when cells are separated with a semi-porous membrane. Furthermore, ILC2 are able to enhance T cell responses in vivo in the lungs of BALB/c mice. Discussion: These data demonstrate that ILC2 are able to drive a Th2-phenotype in naïve Th cells directly. Furthermore, this effect is contact-dependent. These data demonstrate for the first time that ILC2 are capable of driving type-2 immune responses by influencing Th cell responses and hence provide an important link between lung innate and adaptive immune responses and a possible novel mechanism for their role in asthma.